Treatment with IgM‐enriched intravenous immunoglobulins enhances clearance of stroke‐associated bacterial lung infection. Issue 4 (9th August 2022) - McCulloch, Laura; Harris, Alison J.; Malbon, Alexandra; Daniels, Michael J. D.; Younas, Mehwish; Grainger, John R.; Allan, Stuart M.; Smith, Craig J.; McColl, Barry W.
Abstract: Post‐stroke infection is a common complication of stroke that is associated with poor outcome. We previously reported that stroke induces an ablation of multiple sub‐populations of B cells and reduces levels of immunoglobulin M (IgM) antibody, which coincides with the development of spontaneous bacterial pneumonia. The loss of IgM after stroke could be an important determinant of infection susceptibility and highlights this pathway as a target for intervention. We treated mice with a replacement dose of IgM‐enriched intravenous immunoglobulin (IgM‐IVIg) prior to and 24 h after middle cerebral artery occlusion (MCAO) and allowed them to recover for 2‐ or 5‐day post‐surgery. Treatment with IgM‐IVIg enhanced bacterial clearance from the lung after MCAO and improved lung pathology but did not impact brain infarct volume. IgM‐IVIg treatment induced immunomodulatory effects systemically, including rescue of splenic plasma B cell numbers and endogenous mouse IgM and IgA circulating immunoglobulin concentrations that were reduced by MCAO. Treatment attenuated MCAO‐induced elevation of selected pro‐inflammatory cytokines in the lung. IgM‐IVIg treatment did not increase the number of lung mononuclear phagocytes or directly modulate macrophage phagocytic capacity but enhanced phagocytosis of Staphylococcus aureus bioparticles in vitro. Low‐dose IgM‐IVIg contributes to increased clearance of spontaneous lung bacteria after MCAO likely via increasing availability of antibody in the lung to enhance opsonophagocytic activity. Immunomodulatory effects of IgM‐IVIg treatment may also contribute to reduced levels of damage in the lung after MCAO. IgM‐IVIg shows promise as an antibacterial and immunomodulatory agent to use in the treatment of post‐stroke infection. Abstract : IgM‐IVIg improves bacterial lung infection after stroke by enhancing clearance of bacteria, reducing pro‐inflammatory cytokines and pathology in the lung and rescuing mouse plasma cell numbers and mouse IgM production.